The Access to Justice for Indonesian Migrant Workers (in Malaysia, Saudi Arabia and Hongkong) - et. al, Dr. Yayan Sopyan (International Journal of Advanced Science and Technology, 2020)
Many Indonesian migrant workers have deployed to various Middle-Eastern and Asian countries. Each year, they choose to seek employment abroad with a wide varietyof jobs in order to earn their living and change the life hardship in their home country. Malaysia, Saudi Arabia, and Hongkong are the most favorable countries for migrant workers, yet they have many problems. Many research related to migrant workers conducted previously were mostly about the illegal workers, human trafficking, violence, and low salary issues.This research will focus on problem in legal identity - marriage license, divorce certificate, and birth certificate - which is one of the biggest issues in international labour migration. Through socio-legal approaches, this research will elaborate the problems deeply and provide solutions for Indonesian government to enact laws and public policy which support migrant workers’ rights.